Desain busana siap pakai manipulatif untuk perempuan plus size berbasis Wastra Nusantara - Pramesiwi, Vashtia Hanin; Wening, Sri; Jerusalem, Mohammad Adam (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2025)
Plus size bodies present a distinct challenge for women in finding ready to wear clothing that fits their body needs. This study aims to: (1) describe the design planning process and needs in developing ready to wear clothing using Wastra Nusantara (Indonesian traditional textiles) for plus size women; (2) describe the quality of the developed clothing products based on expert evaluations; and (3) describe the level of user preference for the ready to wear products. This is a Research and Development (R&D) study employing the Planning, Production, Evaluation (PPE) development model. The research subjects were 20 women in Magelang Regency aged 20 years and above with a Body Mass Index (BMI) >25 kg/m². The research instrument used a closed ended questionnaire, and the data were analyzed using descriptive statistical techniques. The study produced ready to wear clothing that takes into account design aspects aimed at visually manipulating the body shape of plus size women. The results of the study show that the highest preference levels of plus size women for ready to wear clothing made from batik and lurik are in terms of color (96%0, motif (94,2%), size (92,8%), silhouette (92,5%), fabric (91,7%), and texture (90,6%). Ready to wear clothing made from batik and lurik can be an excellent choice to enhance the self confidence of plus size women through a visually slimmer appearance, while also contributing to the development of inclusive fashion design with a touch of Wastra Nusantara, which has not been widely applied in the plus size women’s segment in Indonesia.